1993
DOI: 10.3904/kjim.1993.8.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori Infection in Patients with Peptic Ulcer Diseases and Non-Ulcer Dyspepsia

Abstract: Background:Helicobacter pylori is known to be a cause of active chronic gastritis and has been proposed as an etiologic factor in the development of peptic ulcer disease, but controversy continues regarding the pathogenic importance and mechanism. We examined the prevalence of H. pylori infection in patients with peptic ulcers and non-ulcer dyspepsia.Method:749 patients (373 with duodenal ulcer, 303 with gastric ulcer, 73 with non-ulcer dyspepsia) were included. Endoscopic mucosal biopsies were done at antrum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…Various studies show the prevalence of H pylori in NUD patients between 37.3% to 75%. [30][31][32] The so called post-infection functional dyspepsia occurring after acute gastrointestinal infection postulates that infl ammation may cause alterations in the enteric nervous system and visceral sensation by modifying signaling in the brain-gut axis. H pylori induced infl ammation of the gastric mucosa in functional dyspepsia falls into the same logic, suggesting that acute and chronic infl ammation seem to play some role in the functional dyspepsia pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies show the prevalence of H pylori in NUD patients between 37.3% to 75%. [30][31][32] The so called post-infection functional dyspepsia occurring after acute gastrointestinal infection postulates that infl ammation may cause alterations in the enteric nervous system and visceral sensation by modifying signaling in the brain-gut axis. H pylori induced infl ammation of the gastric mucosa in functional dyspepsia falls into the same logic, suggesting that acute and chronic infl ammation seem to play some role in the functional dyspepsia pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…They also collected data on patients with no maintenance therapy and only included patients without NSAID use. It is generally known that the prevalence of H. pylori is higher in duodenal ulcer patients than in those with gastric ulcer [16,17] and this difference may be responsible for the fact that gastric ulcer is somewhat likely to relapse more often after H. pylori eradication. Analysis of background factors of patients with ulcer recurrence showed that gastric ulcer recurrence was more common among patients who smoked, consumed alcohol and used NSAIDs compared with duodenal ulcer patients.…”
Section: Discussionmentioning
confidence: 99%
“…although rather lower prevalence was reported in gastric ulcer patients than the African experience (Lee et al, 1993). It is noteworthy that even patients who had normal findings on endoscopy had a very high prevalence of H. pylori (88.9%).…”
Section: Resultsmentioning
confidence: 75%